Organic depth profiling of C60 and C60/phthalocyanine layers using argon clusters. (5th June 2012) - Mouhib, T.; Poleunis, C.; Möllers, R.; Niehuis, E.; Defrance, P.; Bertrand, P.; Delcorte, A.
<x xml:space="preserve">Abstract</x> Molecular semiconductor devices, such as light‐emitting diodes and photovoltaic cells, have recently received considerable attention because of their compatibility with flexible substrates and large‐area applications. Because of the importance of the interfacial properties for the performance of the devices, these organic (multi)layers constitute an important field of application for molecular depth profiling by SIMS. In this contribution, we investigate the use of C60n+ and Ar1000–2000+ cluster projectiles at different energies (ranging from 2.5 to 20 keV) as sputter ions for the organic depth profiling of fullerene‐based films and heterojunctions. The bilayers consist of C60 fullerenes on tin phthalocyanine (SnPc), deposited on silicon substrates. Our preliminary results showed that C60 films could not be successfully profiled using C60n+ ions in regular analysis conditions (room temperature). In contrast, with Ar clusters, the depth profiling is successful (except for 20 keV Ar1000) and the sputtered volume shows a linear relationship with the Ar cluster energy. Surprisingly, for a given total energy of the projectiles, Ar2000 sputters approximately two times more than Ar1000. The observations are tentatively explained as being the result of a balance between the sputtering and the cross‐linking efficiency for the different bombardment conditions, larger clusters being expected to naturally induce less cross‐linking than smaller clusters with the same total energy. Copyright © 2012 John Wiley & Sons, Ltd.